A comparative study of ionospheric spread-F and scintillation at low- and mid-latitudes in China during the 24th solar cycle. Issue 2 (15th January 2019) - Wang, Ning; Guo, Lixin; Zhao, Zhenwei; Ding, Zonghua; Xu, Tong; Sun, Shuji
Highlights: FSF occurred more often after midnight. RSF and scintillation appeared mainly during pre-midnight. FSF occurrence rates mostly appeared during the summer months. RSF and scintillation occurred mostly in the equinoctial months at low-latitudes. Scintillation occurrence was usually associated with the appearance of RSF. Abstract: The spread-F echo of ionograms and scintillation of satellite signal propagation along the Earth-space path are two typical phenomena induced by ionospheric irregularities. In this study, we obtained spread-F data from HF (high frequency) digital ionosonde and scintillation index (S4) data from L-band and UHF receivers at low- and mid-latitudes in China during the 24th solar cycle. These four sites were located at Haikou (HK) (20°N, 110.34°E), Kunming (KM) (25.64°N, 103.72°E), Qingdao (QD) (36.24°N, 120.42°E), and Manzhouli (MZL) (49.56°N, 117.52°E). We used these data to investigate spread-F and scintillation occurrence percentages and variations with local time, season, latitude and solar activity. A comparative study of spread-F and scintillation occurrence rates has been made. The main conclusions are as follows: (a) FSF occurred mostly during post-midnight, while RSF and scintillation appeared mainly during pre-midnight at HK and KM; (b) FSF occurrence rates were larger at QD and MZL than expected; (c) the FSF occurrence percentages were anti-correlated with solar activity at HK and KM; meanwhile RSF and scintillation occurrence rates increased with the increase of solar activity at this two sites; (d) the highest FSF occurrence rates mostly appeared during the summer months, while RSF and scintillation occurred mostly in the equinoctial months at HK and KM; (e) the scintillation occurrence was usually associated with the appearance of RSF, probably due to a different physical mechanism comparing with FSF. Some of these results verified the conclusions of previous papers, whereas some show slight difference. These results are important in understanding ionospheric irregularities variations characteristic at low- and mid-latitudes in China.